At His Majesty’s Service: Racial Policies, Policing, and Revolutionaries in Pacific Canada - Caron, Matthieu (Cahiers d'histoire, 2016)
This article highlights the events that led up to the 1914 Komagata Maru incident arguing that racialized Canadian politics of migration fuelled Indian anti-colonialism on the Pacific slope. The sequence of events, from the turn of the century to 1914, is examined within the scope of Canadian race relations as a member of the British Empire. Central to the events is the systematic policing and surveillance of the racialized “Other.” Of particularly interest in this article, and in the implementation of Canada’s Pacific system of surveillance, is the fact that the monitoring, policing, and surveillance of Indian revolutionaries in Canada was the undertaking of a single individual, William Charles Hopkinson, who was himself of Indian descendant, and therefore a racialized Other.